2006
DOI: 10.4315/0362-028x-69.5.990
|View full text |Cite
|
Sign up to set email alerts
|

Survival of a Five-Strain Cocktail of Escherichia coli O157:H7 during the 60-Day Aging Period of Cheddar Cheese Made from Unpasteurized Milk

Abstract: The U.S. Food and Drug Administration Standard of Identity for Cheddar cheeses requires pasteurization of the milk, or as an alternative treatment, a minimum 60-day aging at > or =2 degrees C for cheeses made from unpasteurized milk, to reduce the number of viable pathogens that may be present to an acceptable risk. The objective of this study was to investigate the adequacy of the 60-day minimum aging to reduce the numbers of viable pathogens and evaluate milk subpasteurization heat treatment as a process to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 15 publications
3
53
0
Order By: Relevance
“…However, the rate of increase in STEC for the BTC and the two UPCs (approximately 0.5 to 2.5 log 10 CFU · g Ϫ1 , depending on the cheese-making scheme and serotype) clearly indicates bacterial growth. Schlesser et al (24) have also observed a 1-to 2-log 10 -CFU · g Ϫ1 increase in an artificially inoculated cocktail of E. coli O157:H7 during cheddar cheese-making operations. At the initial stages of preparation of the BTC and the two UPCs, the temperature (Ͼ30°C) is ideal for STEC growth and the moderate acidification can only slow down this growth.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…However, the rate of increase in STEC for the BTC and the two UPCs (approximately 0.5 to 2.5 log 10 CFU · g Ϫ1 , depending on the cheese-making scheme and serotype) clearly indicates bacterial growth. Schlesser et al (24) have also observed a 1-to 2-log 10 -CFU · g Ϫ1 increase in an artificially inoculated cocktail of E. coli O157:H7 during cheddar cheese-making operations. At the initial stages of preparation of the BTC and the two UPCs, the temperature (Ͼ30°C) is ideal for STEC growth and the moderate acidification can only slow down this growth.…”
Section: Discussionmentioning
confidence: 89%
“…The presence of pathogenic bacteria, including STEC, in cheeses is a major concern for food safety authorities. To address the problem, the U.S. Food and Drug Administration requires a minimum of 60 days' aging for cheeses made from unpasteurized milk (23,24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A five-strain cocktail of a pathogen species was added to 1-liter water samples. Multiple-strain cocktails are commonly used in human and plant pathogen studies for more comprehensive assessments because it is common for more than one strain to be present in a food-borne illness or plant disease outbreak (22,23). Bacterial cocktails were produced by adding 10 ml of stationary-phase culture of each strain together and thor- …”
Section: Methodsmentioning
confidence: 99%
“…In addition, the 1987 FDA ban on interstate raw dairy transport allows for an exception of cheese made from raw milk, provided the cheese has been aged a minimum of 60 days and is clearly labeled as unpasteurized. However, there is evidence that E coli can survive in cheese products even after a 60-day aging period, 29 and recent outbreaks of E coli O157 illness associated with such unpasteurized, aged cheese have been documented in Arizona, California, Colorado, and New Mexico. 30 …”
Section: Guidelines For Sales Of Raw or Unpasteurized Milk And Milk Pmentioning
confidence: 99%